(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study presents findings from experiments assessing the feasibility of utilizing egg shell powder, sourced from the egg shell, periwinkle, palm kernel fibre and saw dust, for improving cement sheet contraction. Cement slurries serve critical functions, such as facilitating zonal isolation, safeguarding the casing against corrosion, absorbing shock loads encountered during deeper drilling, and preventing blowouts by rapidly establishing a seal. The effectiveness and successful execution of cementing operations heavily rely on specific properties of the slurry, which can be enhanced through the incorporation of various additives. This study focuses on examining the impact of various local additives, including Palm kernel fibre aggregates and Silica sand, on specific properties of cement slurry. The conducted tests revealed that the cement samples mixed with local additives exhibited compressive strengths that ranged from a minimum of 3,359 psi to 11,759 psi, in contrast to the plain class G slurry, which registered an unsuitable strength of 1,600 psi. Additionally, the density measurements were found to be acceptable, falling between 15.3 and 16 ppg. However, the rheological properties and fluid loss characteristics were assessed to be either standard or subpar when compared to the benchmarks established by the American Society for Testing and Materials (ASTM). Upon concluding the experiment, a noticeable difference was noted between the results of the neat class G slurry and those of the additive-mix slurries. Consequently, it was determined that the neat slurry sample served effectively as a fluid loss agent, while all samples, with the exception of the plain slurry, demonstrated satisfactory compressive strengths. Additionally, the palm fibre alone showed sufficient rheological properties; however, with the sole exception of the plain slurry, none of the samples proved to be effective fluid loss agents.